1995
DOI: 10.1515/bchm3.1995.376.10.611
|View full text |Cite
|
Sign up to set email alerts
|

The Baculovirus Cysteine Protease Has a Cathepsin B-like S2-Subsite Specificity

Abstract: Autographa californica nuclear polyhedrosis virus (AcNPV) encodes a functional cysteine protease of the papain family which is expressed after infection in Spodoptera fruglperda Sf9 cells. The protease displays an inhibition profile typical for cysteine proteases and is highly active against synthetic peptide substrates. The pH optimum of the bell-shaped pH-activity curve is between 5.0 and 5.5. The best substrate tested is Z-Arg-Arg-MCA which is specific for cathepsin B. The specificity constant (Kcat/Km) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…This suggested that either MASP-3 underwent self-activation, or that extrinsic activation was mediated by a contaminating protease from the host cell system. In this respect, the presence of cysteine protease activity in the supernatant of baculovirus-infected insect cells has been reported in several studies (42)(43)(44)(45). One of these reports describes a baculovirus cathepsin-like cysteine protease with the ability to cleave peptide substrates with an Arg residue at the P1 position (43), which may account for the cleavage of the Arg 440 -Ile 441 bond of MASP-3.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This suggested that either MASP-3 underwent self-activation, or that extrinsic activation was mediated by a contaminating protease from the host cell system. In this respect, the presence of cysteine protease activity in the supernatant of baculovirus-infected insect cells has been reported in several studies (42)(43)(44)(45). One of these reports describes a baculovirus cathepsin-like cysteine protease with the ability to cleave peptide substrates with an Arg residue at the P1 position (43), which may account for the cleavage of the Arg 440 -Ile 441 bond of MASP-3.…”
Section: Discussionmentioning
confidence: 94%
“…In this respect, the presence of cysteine protease activity in the supernatant of baculovirus-infected insect cells has been reported in several studies (42)(43)(44)(45). One of these reports describes a baculovirus cathepsin-like cysteine protease with the ability to cleave peptide substrates with an Arg residue at the P1 position (43), which may account for the cleavage of the Arg 440 -Ile 441 bond of MASP-3. This hypothesis would be consistent with the lack of proteolytic activity observed at 37°C, considering that insect cells are grown at 27-28°C and are not viable at 37°C.…”
Section: Discussionmentioning
confidence: 94%
“…The AcMNPV cysteine protease is expressed as a precursor form which is processed to a 27n5 kDa mature form. At the sequence level, the baculovirus cysteine proteases most closely resemble cathepsins L and\or H, but detailed characterization of the substrate specificity of AcMNPV cathepsin suggests that its activity more closely resembles cathepsin B (Ohkawa et al, 1994 ;Bro$ mme & Okamoto, 1995 ;Slack et al, 1995). Deletion of either the cathepsin (cath) or chiA genes results in failure of the virus to cause liquefaction of the host, indicating that the proteins function together to promote degradation of host tissues at the end of the infection process (Ohkawa et al, 1994 ;Slack et al, 1995 ;Hawtin et al, 1997 ;Suzuki et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…We however found that the furin inhibitor, Dec-RVKR-CMK, did not affect per os infection of AcMNPV to T. ni larvae (data not shown). R195/R196 is also a preferred cleavage site motif for the baculovirus protease, V-CATH (Bromme & Okamoto, 1995). V-CATH is produced at the end of infection and aids release of OBs (Ohkawa et al, 1994;Slack et al, 1995).…”
Section: Discussionmentioning
confidence: 99%